Cognitive function and behavioral problems in children born to mothers with preeclampsia: an Indian study. Issue 3 (3rd April 2022) - Koparkar, Shruti; Srivastava, Leena; Randhir, Karuna; Dangat, Kamini; Pisal, Hemlata; Kadam, Vrushali; Malshe, Nandini; Wadhwani, Nisha; Lalwani, Sanjay; Srinivasan, K.; Kumaran, K.; Fall, Caroline; et al.
ABSTRACT: Studies from high-income countries report associations of preeclampsia (PE) with reduced cognitive function and adverse behavioural outcomes in children. We examined these associations in Indian children aged 5-7 years. Children of mothers with PE (n=74) and without PE (non-PE; n=234) were recruited at delivery at Bharati Hospital, Pune, India. The cognitive performance was assessed using 3 core tests from the Kaufman Assessment Battery and additional tests including Verbal fluency, Kohs block design, and Coding A (from Wechsler Intelligence Scale for Children). The parent-reported Strengths and Difficulties Questionnaire (SDQ) was used to assess children's behavioral characteristics. Scores were compared between children from PE and non-PE groups, and associations analyzed further using regression models, adjusted for potential confounders. After adjusting for age, sex, socio-economic status and maternal education, children of PE mothers had lower Kohs block design scores (adjusted odds ratio per score category 0.57, [95% CI 0.34-0.96] p=0.034; 0.62 [95%CI (0.36, 1.07), p=0.09 on further adjustment for birth weight and gestation) compared to children of mothers without PE. In the SDQ, there was a lower prevalence of abnormal 'conduct problem' scores in PE group than non-PE group (OR=0.33, 95% CI 0.13-0.83, p=0.018, in the fully adjusted model); there were no differences for other behavioral domains. This preliminary study in Indian children suggests that fetal exposure to maternal PE may have an adverse impact on visuo-spatial performance but does not adversely affect behavior. Further studies with larger sample sizes are essential to understand effects of maternal PE on cognitive/behavioral outcomes in children.